The Essential Oil Composition of Tanacetum densum (Labill.) Heywood ssp sivasicum Hub.-Mor. & Grierson from Turkey - Polatoglu, Kaan; Goren, Nezhun; Baser, K. Huesnue Can; Demirci, Betuel (TAYLOR & FRANCIS INC, 2009)
Water-distilled essential oils from the aerial parts of Tanacetum densum (L.) Heywood ssp. sivasicum Hub.-Mor. et Grierson from Turkey were analyzed by GC and GC/MS. Tanacetum densum ssp. sivasicum flower and stem oils were characterized with 1,8-cineole (21.1% and 28.3%, respectively), camphor (19.2% and 16.4%, respectively), and borneol (5.8% and 6.4%, respectively).
Keywords: Tanacetum densum ssp sivasicum; Compositae; essential oil composition; 1,8-cineole; camphor; SUBSP SIVASICUM; BALSAMITA L.; SCHULTZ BIP.; IRAN; CONSTITUENTS; Chemistry; Food Science & Technology